Review. Carlos Mauricio Hernández. La civilización fracasada. Crítica política desde Ignacio Ellacuría al capitalismo. San Cristóbal de Las Casas: Universidad Nacional Autónoma de México, Centro de Investigaciones Multidisciplinarias sobre Chiapas (Palimpsesto, 2023)
Critical review of the book The failed civilization. Political criticism from Ignacio Ellacuría to the capitalism of Carlos Mauricio Hernández in which the successes of the revision and some absences in this regard are highlighted. The reflections that Hernández highlights on the failure of capitalist civilization from the Eellacuríano thought are compared with political scientists, such as Carl Schmitt and anthropologists such as Bruno Latour and Marshal Sahlins in their considerations on secularization and the failure of the project of modernity.
Keywords: Capitalism; Critical T; thought; Ellacuría; El Salvador; Poverty culture